2021
DOI: 10.1002/vrc2.208
|View full text |Cite
|
Sign up to set email alerts
|

Nerve stimulation‐guided femoral and sciatic blocks in an alpaca (Vicugna pacos) for the removal of a sequestrum from the distal femur

Abstract: A 2‐year‐old female intact huacaya alpaca weighing 66.6 kg presented for the removal of a bone sequestrum from the distal femur. Nerve stimulator‐guided femoral and sciatic nerve blocks were applied to provide analgesia for distal femoral surgery. The blocks were simple to perform using existing equipment and current techniques translated from small animals. The techniques reported here for both femoral and sciatic nerve blocks in an alpaca can be used as an alternative to an ultrasound‐guided approach, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Therefore, interest in locoregional anaesthesia in other species is growing 25–27 . Locoregional anaesthesia for the hindlimb has been reported in alpacas, where two electrostimulation‐guided sciatic and femoral nerve blocks were performed for distal femur or stifle surgery 11,12 . In both cases, boluses of morphine 0.1 mg/kg were necessary during the surgery due to cardiovascular increments during maintenance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, interest in locoregional anaesthesia in other species is growing 25–27 . Locoregional anaesthesia for the hindlimb has been reported in alpacas, where two electrostimulation‐guided sciatic and femoral nerve blocks were performed for distal femur or stifle surgery 11,12 . In both cases, boluses of morphine 0.1 mg/kg were necessary during the surgery due to cardiovascular increments during maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that ketamine and lidocaine infusions decreased sevoflurane minimum alveolar concentration in alpacas without adverse effects during the recovery period 36 . In addition, if extra analgesia is required, intraoperative morphine administration can be used 11,12 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations